THE MAIN WAYS OF IMPROVING INTER-RELIGIOUS RELATIONS IN KAZAKHSTAN SOCIETY - Кokeyeva, Д М (Journal of Oriental Studies, 2016)
This article explains the main ways of improving inter-religious relations in Kazakhstan society. Also carefully analyzed the religious changes that have resulted from the influence of modern processes of religion.